2024
DOI: 10.1021/jacs.4c01218
|View full text |Cite
|
Sign up to set email alerts
|

Single-Pore Nanofluidic Logic Memristor with Reconfigurable Synaptic Functions and Designable Combinations

Yixin Ling,
Lejian Yu,
Ziwen Guo
et al.

Abstract: The biological neural network is a highly efficient inmemory computing system that integrates memory and logical computing functions within synapses. Moreover, reconfiguration by environmental chemical signals endows biological neural networks with dynamic multifunctions and enhanced efficiency. Nanofluidic memristors have emerged as promising candidates for mimicking synaptic functions, owing to their similarity to synapses in the underlying mechanisms of ion signaling in ion channels. However, realizing chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…The memristor, an abbreviation of memory-resistor, was first proposed by Chua that connects the electric charge and magnetic flux linkage. As the fourth fundamental circuit element besides resistor, capacitor, and inductor, , the memristor shows its significance for brain-inspired neuromorphic computing and biomachine interfaces with high efficiency and low energy consumption. Recently, electrolyte ionic memristors emerged and showed promising features of emulating voltage-gated ionic neural functions in water systems. …”
mentioning
confidence: 99%
“…The memristor, an abbreviation of memory-resistor, was first proposed by Chua that connects the electric charge and magnetic flux linkage. As the fourth fundamental circuit element besides resistor, capacitor, and inductor, , the memristor shows its significance for brain-inspired neuromorphic computing and biomachine interfaces with high efficiency and low energy consumption. Recently, electrolyte ionic memristors emerged and showed promising features of emulating voltage-gated ionic neural functions in water systems. …”
mentioning
confidence: 99%
“…The memristive effects observed allow for a neuromorphic-like potentiation of the membrane conductance that is regulated by voltage pulses. Also, we have suggested that arrangements of memristive membranes could be employed in the design of electrochemical circuits for implementing logic functions and information processing in iontronics. , …”
mentioning
confidence: 99%